Analysis of the performance and scalability of microservices depending on the communication technology - Jan Jarmoszewicz; Patryk Iwanowski; Małgorzata Plechawska-Wójcik (Journal of Computer Sciences Institute)
The aim of this study is to compare the performance and scalability of microservices based on the communication technology used. The research is conducted on four systems, each consisting of three microservices, utilizing REST and gRPC technologies, as well as two communication schemes between the services. The systems are tested on two experimental setups with different system resources, considering metrics such as response time, memory usage, and CPU usage. The obtained results indicate that applications based on gRPC are generally more efficient and scalable but require more CPU resources, whereas REST-based applications require more RAM resources.